The impact of climate disaster risk on agricultural trade welfare and coping strategies from a global perspective - Zhang, Zhimin; Li, Chenguang; Yuan, Jiahui; Wang, Xiaojuan (Frontiers in Sustainable Food Systems, 2025)
As one of the most significant global challenges of the 21st century, climate change has had a substantial impact on global agricultural production and trade. This paper adopts an empirical approach to examine the impact of climate disaster risk on the welfare of global agricultural trade across 114 countries, as measured by the varieties-corrected terms of trade from 2002 to 2021. The study finds that, over the past two decades, the terms of trade for agricultural products have improved in 50 countries. In contrast, the terms of trade for agricultural products have worsened in 22 countries. Additionally, the terms of trade for 42 countries have exhibited volatility. Moreover, climate disaster risk has the potential to boost agricultural trade welfare in the short term. However, in the long term, such risk leads to supply constraints and lower trade welfare in global markets by disrupting supply chains. Specifically, the agricultural trade welfare of highly open economies, non-high-income countries, and those relying on primary agricultural products is more susceptible to adverse shocks caused by climate disaster risk. This study offers new insights into addressing climate change and ensuring the stability and growth of global agricultural trade welfare.